Testing candidate genes for attention-deficit/hyperactivity disorder in fruit flies using a high throughput assay for complex behavior. Issue 1 (2nd January 2016) - Rohde, Palle Duun; Madsen, Lisbeth Strøm; Neumann Arvidson, Sandra Marie; Loeschcke, Volker; Demontis, Ditte; Kristensen, Torsten Nygaard
Abstract: Fruit flies are important model organisms for functional testing of candidate genes in multiple disciplines, including the study of human diseases. Here we use a high-throughput locomotor activity assay to test the response on activity behavior of gene disruption in Drosophila melanogaster . The aim was to investigate the impact of disruption of 14 candidate genes for human attention-deficit/hyperactivity disorder (ADHD) on fly behavior. By obtaining a range of correlated measures describing the space of variables for behavioral activity we show, that some mutants display similar phenotypic responses, and furthermore, that the genes disrupted in those mutants had common molecular functions; namely processes related to cGMP activity, cation channels and serotonin receptors. All but one of the candidate genes resulted in aberrant behavioral activity, suggesting involvement of these genes in behavioral activity in fruit flies. Results provide additional support for the investigated genes being risk candidate genes for ADHD in humans.